The Role of Southeast Sulawesi Government in Advocating Special Education Access for Disabled Peopl - Misnawaty Lily (International Journal Labs, 2021)
Compared to the other issues, such as infrastructure development, poverty, and others, the equal education for disabled people has not been addressed fully. The purpose of this study is to describe the problems of access to education for students with disabilities in the region of the Regional Government of the Southeast Sulawesi Province, to understand policy taken by the Regional Government as well as to identify obstacles in implementing it. This research was conducted through interviews with several staffs of the Regional Government of the Southeast Sulawesi Province and literature study through books, journals, news and other related sources that can support this research. Through analysis using human rights theory, it is known that the Regional Government of the Southeast Sulawesi Province succeeded in helping to fulfill the existence of human rights service by drafting a regional regulation on the rights of persons with disabilities. However, the implementation of the regulation still faces obstacles such as a lack of understanding by teachers or school staffs about the definition of disability and inclusive education. In addition, the facilities and teaching staff for inclusive education systems and special schools are also still very limited, especially during the pandemic.